Dissecting the Genotypic and Environmental Factors Underpinning the Quantitative Trait Variation in a Set of Wild Tomato (Solanum habrochaites LA1777) Introgression Lines - Pasquale Tripodi; Antonella Vitiello; Bruno D’Onofrio; Mario Parisi; Maria Cammareri (Agronomy, 2020)
Exotic libraries have proven a powerful tool for the exploitation of wild relatives and quantitative trait loci (QTLs) detection in crop species. In early 2000, an introgression line (IL) population of the wild tomato Solanum habrochaites (SH) acc. LA1777 was developed and made publicly available. Despite the potentiality of the donor parent, so far, these lines have been poorly explored for their agronomic performance and for the identification of genomic regions underlying the variation of quantitative traits (QTLs). Here, we report the evaluation of 19 morpho-agronomic and chemical traits on a set of 39 ILs grown in three consecutive field seasons with the aim to: (a) Determine the overall phenotypic performances of the studied collection, (b) estimate the influence of the genotype (G) and the year of cultivation (Y) and their interaction on the traits analyzed, (c) investigate the plasticity of the traits, and (d) identify whole-genome QTLs in the wild SH background. The ILs showed lower productivity compared to the control genotype, while no major effects were found for the morphological fruit-related traits. Instead, a general increase in the soluble solids content was observed. The combined analysis of G × Y highlighted a major effect of the genotype on trait variation, although yield-related traits were more influenced by environmental factors. In total, 75 associations for 17 traits were detected. Major QTLs increasing soluble solids, pericarp thickness, and trichome density were respectively found on chromosomes 1, 5, and 11 with a percentage variation (PV) of 24.01%, 32.49%, and 200%. Furthermore, different QTLs increasing the color intensity and fruit shape were detected. These results suggest that SH could be a potential source of favorable alleles for qualitative traits despite its inferior phenotype compared to the cultivated parent. The evaluated set of SH LA1777 ILs is a potential for novel allele discovery in wild tomatoes and for breeding purposes towards the exploitation of the available introgressions and for the pyramiding of traits.